2018
DOI: 10.18632/aging.101557
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the anti-aging and prolongevity effects of caloric restriction: evidence from studies of genetically modified animals

Abstract: It is widely accepted that caloric restriction (CR) extends lifespan and suppresses various pathophysiological changes. CR suppresses growth hormone/insulin-like growth factor signaling and mechanistic target of rapamycin complex 1 activity, activates sirtuin and enhances mitochondrial redox regulation, but the exact mechanisms are still under debate. In this review, we discuss the mechanisms of CR using evidence from studies of animals that were genetically modified according to recent advances in molecular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Previous research has reported a link between sirtuins and mitochondrial function and abnormal tau proteins and amyloid. It was confirmed that SIRT1, 3, and 6 are involved in age-related disease and regulation of life span, as well as AD progression ( Hoshino et al, 2018 ). In mice model of AD, accompanied by impaired DNA repair, the precursor of NAD + , nicotinamide riboside (NR), increases SIRT3 and SIRT6 ( Hou et al, 2018 ).…”
Section: Calorie Restriction and Cognitive And Social Determinants Ofmentioning
confidence: 90%
“…Previous research has reported a link between sirtuins and mitochondrial function and abnormal tau proteins and amyloid. It was confirmed that SIRT1, 3, and 6 are involved in age-related disease and regulation of life span, as well as AD progression ( Hoshino et al, 2018 ). In mice model of AD, accompanied by impaired DNA repair, the precursor of NAD + , nicotinamide riboside (NR), increases SIRT3 and SIRT6 ( Hou et al, 2018 ).…”
Section: Calorie Restriction and Cognitive And Social Determinants Ofmentioning
confidence: 90%
“…Although there is no system equivalent to GH in lower organisms such as yeast, worms, and flies [120], a number of observations reported for the last two decades strongly support the idea that downregulation of IIS and activation of FOXO transcription factors extend lifespan in these animal models (reviewed in [120,159,162,163]). In fact, of the > 40 genetic mutations that have been reported to extend lifespan in the mouse and the rat models, approximately one third of them are involved in GH and IIS [164]. Because CR reduces GH and IIS [164], it is generally accepted that CR extends lifespan by limiting GH/IIS signaling and subsequently expressing pro-longevity genes by activating FOXO transcription factors [165].…”
Section: Iis-foxo Signalingmentioning
confidence: 99%
“…In fact, of the > 40 genetic mutations that have been reported to extend lifespan in the mouse and the rat models, approximately one third of them are involved in GH and IIS [164]. Because CR reduces GH and IIS [164], it is generally accepted that CR extends lifespan by limiting GH/IIS signaling and subsequently expressing pro-longevity genes by activating FOXO transcription factors [165]. To date, there are mixed results reported for the question of whether the IIS-FOXO signaling cascade is responsible for CR-mediated lifespan extension.…”
Section: Iis-foxo Signalingmentioning
confidence: 99%
“…The animals that emerge from dauer undergo rapid catch-up development to achieve reproductive maturity in a few days and eventually die at the usual developmental age in 1-2 weeks. Caloric restriction in vertebrates produces a similar slowing of the biological clock associated with aging [27,86].…”
Section: Hyperpurinergic Hypometabolism and The Biological Clocks Of mentioning
confidence: 99%